Inclusive schools: Are teachers adequately prepared for inclusion? - Divon, Dikla (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
This article will discuss one of the main topics on the educational and social agendas in Israel. Integrating children and adults with special needs into schools and the community is a worldwide issue. Many researchers have tried to find and evaluate the most effective integration methods, to assist people with special needs and enable them high quality of life and equality. In this article, we will look at the process of integrating students with special needs and the transition that took place during the last few decades regarding the idea of “inclusion”, which is now a top priority for the Ministry of Education’s directors. Based on recent studies, we will examine whether school teaching staff and student teachers are ready to implement inclusive programs in schools as required. We will then propose ways to optimize the training of the educational staff, towards the implementation of the inclusive programs.